PEMANTAUAN DINAMIKA TINGGI MUKA AIR SECARA OTOMATIS DI LAHAN GAMBUT - Nur Wakhid; Zainudin Zainudin (EnviroScienteae, 2019)
Ground Water level fluctuation data on tropical peatland is necessary to restore the degraded peatlands as well as for peatland sustainable management. Peatland restoration always begins with groundwater level restoration (GWL). Therefore, measurement of GWL is necessary for further management. GWL fluctuation on peat soil greatly varies even during a day, therefore automatic GWL measurements are inevitably needed. This study aim is to develop an automatic GWL measurement (TMA) by comparing 2 automatic water level loggers in tropical peatlands. This research was conducted in a rubber plantation on Peat Soil I in Jabiren, Pulang Pisau, Central Kalimantan, from February to December 2014. The measurement of GWL was conducted by manual measurement and using 2 automatic water level monitoring devices. Automatic GWL measurement showed a more detail variation than that of manual measurement. The different of GWL between manual, automatic 1 and 2 were on the range of 16-30 cm. Automatic measurement instruments that users were having their advantages or disadvantages, with the result of measurements were significantly different.